Corporate reporting: how words add value - Moll, Gabriele (Language at Work - Bridging Theory and Practice, 2007)
The primary function of corporate reporting is to provide investors with information. However, these days, companies are also recognising the media value of the annual report, which is the main vehicle of corporate reporting, and are concluding that it’s an efficient means of communication between the business and their stakeholders. Corporate reporting also assists in building image. Additionally in recent years there has been an increasing trend in value reporting, which can be defined as: a new form of reporting where words are as important as figures.